Supplemental food alters nest defence and incubation behaviour of an open‐nesting wetland songbird. (13th August 2018) - Vafidis, Jim O.; Facey, Richard J.; Leech, David; Thomas, Robert J.
Abstract : Climate‐driven increases in spring temperatures are expected to result in higher prey availability earlier in the breeding season for insectivorous birds breeding in wetland habitats. Predation during the incubation phase is a major cause of nesting failure in open‐nesting altricial birds such as the Eurasian reed warbler. The nest predation rate in this species has recently been shown to be substantially reduced under conditions of experimentally elevated invertebrate prey availability. Food availability near the nest may be an important determinant of adult incubation and nest defence behaviours during the incubation period. We used two experimental studies to compare incubation behaviour and nest defence in food‐supplemented and unsupplemented adult Eurasian reed warblers during the incubation phase. In the first study we measured nest defence behavioural responses to a taxidermic mount of a native predator (stoat Mustela erminea ). In the second study we used temperature loggers installed in nests to measure breaks in incubation as a measure of nest vulnerability. Food‐supplemented birds responded aggressively to the presence of a predator more quickly than those in the unsupplemented group, suggesting they are closer to their nest and can more quickly detect a predator in the vicinity. Food‐supplemented birds also had shorter breaks in incubation (both in terms of maximum and mean off‐bout durations), presumably because they were foraging for shorter periods or over shorter distances from the nest. This study therefore identifies the behavioural mechanisms by which changes in food availability may lead to changes in nest survival and thus breeding productivity, in open‐nesting insectivorous birds.